2014
DOI: 10.1089/brain.2014.0264
|View full text |Cite
|
Sign up to set email alerts
|

Abstinence from Cocaine and Sucrose Self-Administration Reveals Altered Mesocorticolimbic Circuit Connectivity by Resting State MRI

Abstract: Previous preclinical studies have emphasized that drugs of abuse, through actions within and between mesocorticolimbic (MCL) regions, usurp learning and memory processes normally involved in the pursuit of natural rewards. To distinguish MCL circuit pathobiological neuroadaptations that accompany addiction from general learning processes associated with natural reward, we trained two groups of rats to self-administer either cocaine (IV) or sucrose (orally) followed by an identically enforced 30 day abstinence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 77 publications
(98 reference statements)
5
28
1
1
Order By: Relevance
“…Significant coherent BOLD activity occurred with structures near the vicinity (within several slices) of seed regions. However, in general, these followed a connectivity pattern that is consistent with published studies (Jonckers et al, 2014;Lu et al, 2012bLu et al, , 2014Pawela et al, 2008). Importantly, comparisons of in vivo functional connectivity patterns to functional connectivity patterns in fresh and fixed post-mortem brain tissue indicate that the patterns are not the result of technical artifacts arising from image acquisition (radiofrequency, gradient noise, etc.)…”
Section: Detection Of Rat Brain Network Functional Connectivity Usingsupporting
confidence: 85%
See 1 more Smart Citation
“…Significant coherent BOLD activity occurred with structures near the vicinity (within several slices) of seed regions. However, in general, these followed a connectivity pattern that is consistent with published studies (Jonckers et al, 2014;Lu et al, 2012bLu et al, , 2014Pawela et al, 2008). Importantly, comparisons of in vivo functional connectivity patterns to functional connectivity patterns in fresh and fixed post-mortem brain tissue indicate that the patterns are not the result of technical artifacts arising from image acquisition (radiofrequency, gradient noise, etc.)…”
Section: Detection Of Rat Brain Network Functional Connectivity Usingsupporting
confidence: 85%
“…Functional MRI studies in rats indicated that cocaine increases neural activity in the prefrontal cortex, and in the nucleus accumbens (NAc) and dorsal striatum (Febo et al, 2004a, b;Lu et al, 2012a). Cocaine also reduces functional connectivity in mesolimbic and mesocortical brain areas (Lu et al, 2014), as well as in other non-reward-related brain regions (Li et al, 2000). Therefore, we predicted that MDPV administration would elicit similar reductions in functional connectivity between the NAc and the prefrontal cortex.…”
Section: Introductionmentioning
confidence: 91%
“…Three resting state functional connectivity studies were conducted in rats [19–20] or monkeys [21]. The results are summarized in Table 5.…”
Section: Resting State Functional Connectivity Studies In Animalsmentioning
confidence: 99%
“…I H reduction would result in significant enhancement of local recurrent network activity in cortical networks, presumably through enhanced effectiveness of dendritic synaptic potentials to initiate action potential activity (Magee, 1999; Nolan et al, 2004). Interestingly, recent studies have shown that psychostimulant exposure in animal models of self-administration induces hypoactivity of mPFC similar to what is seen in human addicts (Chen et al, 2013; Lu et al, 2014). Further research needs to be conducted in order to clarify the I H and HCN subunits contribution to METH abuse and dependence.…”
Section: Discussionmentioning
confidence: 74%